Inequality in Medicine: A Call to Analyze by Sex - Zhang Xiwen (SHS Web of Conferences, 2023)
Sexual dimorphism, the differences between males and females, widely exists in various perspectives of physiology. However, for a long period, such differences were not properly addressed in both biomedical research and clinical trials. The ignorance of women’s health led to many tragedies. With more female scientists and doctors and more solid scientific bases regarding the existence of sexual dimorphism, the inclusion of females has become the center of mainstream medicine. However, with the underrepresentation of females in the biomedical field, women currently still have a significantly higher likelihood to suffer from various aversive drug reactions and bear a lower possibility to have effective treatments. To make difference, people inside and outside the biological fields need to call for awareness and advocacy of sex-based research practices continuously. Balanced sample size from both sexes and sex-specific analyses should be the standard requirements for future research. At the same time, they should be used to recalibrate the medication and health guides that were developed from male-only research. The scientific understanding of health and diseases for both sexes will be clear to facilitate the reality of personalized medicine.